Reformasi Politik dan Kewenangan Presiden: Analisis Kritis terhadap Peran Instruksi Presiden dalam Pembentukan Kebijakan Nasional - Katili, Muh Fakhri B.; Moonti, Riyanto; Moonti, Roy Marthen; Kasim, Muslim A. (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Political reform in Indonesia has brought fundamental changes to the structure of state governance and the decision-making process within the executive branch. One of the instruments still frequently utilized by the President to formulate and direct national policy is the Presidential Instruction (Instruksi Presiden/Inpres). Although it is not classified as a formal regulation within the legal hierarchy, Inpres often has wide-reaching implications for the implementation of public policy. This study aims to critically analyze the legal status, function, and limitations of Inpres in the context of Indonesia’s post-reform government system. Using a normative-juridical approach and literature study of statutory regulations and policy documents, the research finds that the use of Inpres in several instances has extended beyond its administrative function and entered the domain of strategic policymaking, which ideally requires formal legislative processes. This raises concerns regarding accountability, transparency, and the limitation of executive power in a democratic rule-of-law state. The study recommends clearer regulation of the scope and function of Inpres to ensure alignment with political reform principles and good governance standards.